Perancangan Sistem Informasi Manajemen Penjualan pada UMKM di Kabupaten Pangkajene dan Kepulauan - Hardianti, Hardianti; Kartini, Yuni; Andalia, Andalia; Jaya, A Tenri; Waworuntu, Ahmad Yusdarwin (Jurnal Manajemen Informatika, Sistem Informasi dan Teknologi Komputer (JUMISTIK), 2025)
This study aims to design and implement a Sales Management Information System (MIS) for UMKM in Pangkajene and Kepulauan Regency to improve efficiency, recording accuracy, and decision-making quality. The main problems are manual transaction recording, which often leads to errors, difficulty in monitoring inventory in real time, and time-consuming reporting. The study employed a Research and Development (R&D) method with qualitative and quantitative approaches. Data were obtained through observation, interviews, documentation, and questionnaires from 10 UMKM using a purposive sampling technique. The system was developed using a web-based PHP and MySQL system using the Waterfall method and tested using Black Box Testing and User Acceptance Testing (UAT). The results showed the system was able to reduce transaction recording time from approximately 5 minutes to approximately 2 minutes, improve inventory accuracy, and generate automated, real-time reports. Analysis showed a 12.89% performance improvement with a user satisfaction rate of approximately 85%. Thus, the web-based sales MIS effectively increases the efficiency and productivity of UMKM. Keywords: Sistem Informasi Manajemen, Penjualan, UMKM, Waterfall, Efisiensi, Web-based System.